Froth! : the science of beer - Denny, Mark, 1953- (Johns Hopkins University Press, 2009)
"Accomplished homebrewer and physicist Mark Denny has crafted a scientifically sound and witty investigation of the physics and chemistry of beer. He recounts and explains the history of and key technological advances in brewing, provides basic instructions for making your own - including a scientific-yet-accessible account of the changes in appearance during each stage of the process - and looks at the fascinating physical phenomena contained within a pint of beer. Along the way he defines the main concepts and terms involved in the process and shows how you can subject the technical aspects of brewing to scientific analysis."--Jacket.